INTEGRASI ANALISIS UJI CETAK NAPAS BERBASIS E-NOSE SEBAGAI SOLUSI BARU DETEKSI DINI PENYAKIT PARU OBSTRUKTIF KRONIK AKIBAT POLUSI UDARA DI LINGKUNGAN RUMAH PADA MASA PANDEMI COVID-19 - Ayers Gilberth Ivano Kalaij (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2022)
Background: Although 64 million people has suffered from COPD, studies have shown that 70% of COPD patients worldwide was underdiagnosed due to many reasons. Adequate and fast detection are crucial in determining prognosis of this disease. However, many lungs function test still have disadvantages and limitations. Covid-19 pandemic era has limited our mobility and increase the risk of household air-pollution exposure which increase the risk of COPD. Thus, alternative solutions are needed to detect and screened household air pollution related COPD patients as fast as possible. Discussion: E-nose technology has been proven to effectively detects various respiratory diseases. This could be the alternative solution to provide COPD diagnostic tests which usually use spirometry with its disadvantages. Breath-print based VOC detection could be sensor biomarker for respiratory diseases, even COPD. If this is integrated with primary care systems in Indonesia during Covid-19 pandemic era, it could be the solution in early detection of COPD. Conclusion: Integration of e-nose based breath-print test is potential to be the solution of early and accurate detection of COPD which are non-invasive and patient-well with its advantages.